Droplet and Aerosol Generation With Mastoidectomy During the COVID-19 Pandemic: Assessment of Baseline Risk and Mitigation Measures With a High-performance Cascade Impactor. Issue 4 (April 2021) - Freiser, Monika E.; Dharmarajan, Harish; Sri Kavya Boorgu, Devi Sai; Sim, Edward S.; Corcoran, Timothy E.; Jabbour, Noel; Chi, David H.
Abstract : Hypothesis: Aerosols are generated during mastoidectomy and mitigation strategies may effectively reduce aerosol spread. Background: An objective understanding of aerosol generation and the effectiveness of mitigation strategies can inform interventions to reduce aerosol risk from mastoidectomy and other open surgeries involving drilling. Methods: Cadaveric and fluorescent three-dimensional printed temporal bone models were drilled under variable conditions and mitigation methods. Aerosol production was measured with a cascade impactor set to detect particle sizes under 14.1 μm. Field contamination was determined with examination under UV light. Results: Drilling of cadaveric bones and three-dimensional models resulted in strongly positive aerosol production, measuring positive in all eight impactor stages for the cadaver trials. This occurred regardless of using coarse or cutting burs, irrigation, a handheld suction, or an additional parked suction. The only mitigation factor that led to a completely negative aerosol result in all eight stages was placing an additional microscope drape to surround the field. Bone dust was scattered in all directions from the drill, including on the microscope, the surgeon, and visually suspended in the air for all but the drape trial. Conclusions: Aerosols are generated with drilling the mastoid. Using an additional microscope drape to cover the surgical field was an effective mitigation strategy to prevent fine aerosol dispersion while drilling. Abstract : Supplemental Digital Content is available in the text